Preventive health actions of female farmers in Semarang regency to anticipate malnutrition - Kuswardinah, Asih; Rahmawati, R., Anshori, M,; Subarniati, Rika; Priyatmojo, Arif Suryo (Opción)
Malnutrition, obesity and non-communicable diseases still frighten Indonesia until 2019. The phenomenon of malnutrition cases of toddlers and school children was quite elevated in female farmers’ families in Semarang Regency, Central Java. This study described female farmers in ¹⁾assessing the facilitative role of Kelompok Wanita Tani (Female Farmers Organization), ²⁾ assessing the effect of the facilitative role of Female Farmers Organization (FFO) on preventive health actions, and ³⁾ assessing preventive health action to anticipate cases of malnutrition risks. The findings of this ex-post-facto research were used to develop strategies to reduce the risk of malnutrition